2023
DOI: 10.3390/ijms241411363
|View full text |Cite
|
Sign up to set email alerts
|

Short Peptides of Innate Immunity Protein Tag7 (PGLYRP1) Selectively Induce Inhibition or Activation of Tumor Cell Death via TNF Receptor

Daria M. Yurkina,
Tatiana N. Sharapova,
Elena A. Romanova
et al.

Abstract: In this study, we have found two peptides of Tag7 (PGLYRP1) protein-17.1A (HRDVQRT) and 17.1B (RSNYVLKG), that have different affinities to the TNFR1 receptor and the Hsp70 protein. Peptide 17.1A is able to inhibit signal transduction through the TNFR1 receptor, and peptide 17.1B can activate this receptor in a complex with Hsp70. Thus, it is possible to modulate the activity of the TNFR1 receptor and further perform its specific inhibition or activation in the treatment of various autoimmune or oncological di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Previously, using limited trypsinolysis, we identified the peptide 17.1-protein Tag7, which causes the bifunctional activity of this TNFR1 ligand: inhibition of the cytotoxic action of TNF or induction of cytotoxic activity using the Hsp70 coactivator. Shortened fragments of this peptide were also identified, responsible for only one function: inhibitory or cytotoxic [34]. Inhibitory peptides had a noticeable protective effect on the development of CFA-dependent autoimmune arthritis [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, using limited trypsinolysis, we identified the peptide 17.1-protein Tag7, which causes the bifunctional activity of this TNFR1 ligand: inhibition of the cytotoxic action of TNF or induction of cytotoxic activity using the Hsp70 coactivator. Shortened fragments of this peptide were also identified, responsible for only one function: inhibitory or cytotoxic [34]. Inhibitory peptides had a noticeable protective effect on the development of CFA-dependent autoimmune arthritis [40].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have identified peptide fragments of the TNFR1 ligand, the Tag7 protein, which performs only one function: either the inhibition of the TNF interaction with the receptor, or the cytotoxic effect on cells in complexes with the Hsp70 protein [34]. It has been shown that anti-TNF antibodies that reduce TNF levels result in a decrease in the development of rheumatoid arthritis and sepsis [28].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Mts1 and Hsp70 compete for binding to Tag7. An excess of Mts1 displaces Hsp70 from the Tag7-Hsp70 complex to form a Tag7-Mts1 complex devoid of cytotoxic activity [ 22 ]. These results suggest that both proteins bind to the same site of the Tag7 molecule.…”
Section: Introductionmentioning
confidence: 99%
“…The next stage of the study was to evaluate the cytotoxic activity of the obtained complexes. It was previously shown that Tag7–Hsp70 and 17.1–Hsp70 complexes are cytotoxic [ 13 ]. As mentioned above, Tag7 is involved in the induction of cytotoxicity by interacting with the TNFR1 receptor, which induces alternative cytotoxic processes, apoptosis and necroptosis.…”
mentioning
confidence: 99%